The Characteristics of Successful Traders - Wójcik, Kinga (Biznesmaniak, 2020)
The purpose of this article is to show how important the role that psychology plays in trading is. Ignoring psychology and focusing only on a technical and fundamental analysis almost never leads to a long-term success in trading. I am going to present features of successful traders, such as discipline, confidence, patience, and composure.